PATH ANALYSIS SEBAGAI SALAH SATU SARANA STATISTIK DALAM PENELITIAN DAN PENGAMBILAN KEPUTUSAN - Sapariyah, - (Fakultas Ekonomi, Universitas Negeri Semarang, 2007)
Each good decision making is the result of valid data analysis process and the appropriate analysis model. One of data analysis models that often used in research and decision making is path analysis model. This path analysis has an objective to explain either direct effect or indirect effect, or total effect from a set of cause variables toward effect variables. Mathematically and statistically, path analysis follows structural function model; to describe the structure of causal relationship between cause variables and effect variables.ÃÂ By using path analysis, for researchers or decision makers can know direct effect, indirect effect and total effect from independent variables toward dependent variables. Besides, path analysis model can decrease the effect of multicolinearity, thus the coefficient value of path analysis partially was better and can solve the real problems from each independent variables toward dependent variables. It means, if the value of path analysis model was not absurd. Thus,ÃÂ the way of decision making by using this model has a very small risk, so the decision will be more accurate.Keywords: Path analysis, direct effect, indirect effect, total effect.